High-strength and high-toughness hydrogel based on nano crosslinking and preparation method thereof

By preparing high-strength and high-toughness hydrogels based on nanocrosslinking, the problems of uneven structure and insufficient mechanical properties of traditional hydrogels are solved, and higher mechanical properties and structural stability are achieved, and their application prospects in the fields of ligament structure and biomaterials are expanded.

CN119708543APending Publication Date: 2025-03-28SHANDONG DONGCHEN ENG PLASTIC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411912688.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional polymer hydrogels are relatively fragile in actual applications due to sparse cross-linking networks, low solid content and uneven structures, which limit their application prospects.

Method used

By preparing high-strength and high-toughness hydrogels based on nanocrosslinking, styrene microsphere emulsions are prepared by reacting raw materials such as styrene monomer, sodium cetyl sulfonate, potassium persulfate and other raw materials in a water bath, and vinyl triethoxysilane, ammonia water, etc. are added as a template. After multiple covalent network crosslinking liquid soaking and light polymerization, a high-strength and high-toughness hydrogel is obtained.

Benefits of technology

The high strength and toughness of hydrogels are achieved, and better mechanical properties and structural stability are provided, with potential application prospects in the fields of ligament structure and biomaterials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708543A_ABST
    Figure CN119708543A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength and high-toughness hydrogel based on nano crosslinking and a preparation method thereof. The preparation method comprises the following steps: stirring a styrene monomer, sodium hexadecyl sulfonate and potassium persulfate to react to prepare a styrene microsphere emulsion; the preparation method comprises the following steps: by taking styrene microspheres as a template, adding vinyltriethoxysilane and ammonia water, carrying out a magnetic stirring reaction to obtain a PS (at) SiO2 microsphere emulsion, washing, centrifuging and drying to obtain inorganic nano microspheres with double bonds on the surfaces, and then sequentially soaking and polymerizing the inorganic nano microspheres in first, second and third types of covalent network cross-linking solutions to obtain the high-molecular-weight self-crosslinking polymer microspheres. The high-strength and high-toughness hydrogel based on nano crosslinking is obtained. According to the preparation method disclosed by the invention, the inorganic nano-microspheres, the three-component covalent cross-linked structure and the non-covalent acting force have a synergistic effect, the technological process is easy to control, the operation is convenient, the reaction condition is mild, the mechanical property of the hydrogel material is remarkably improved, and the hydrogel material has a potential application prospect in the fields of ligament structures, biological materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material preparation, and specifically relates to a high-strength and high-toughness hydrogel based on nano-crosslinking and a preparation method thereof. Background Art

[0002] Polymer hydrogels are considered to be ideal matrices for preparing artificial driving materials and devices such as sensors, artificial muscles, soft actuators, and soft robots, as they have the properties of both liquids and solids, high water content, and good biocompatibility. They have broad application prospects. The nanostructure and mechanical properties of polymer hydrogels are crucial to their applications. Compared with natural materials, traditional polymer hydrogels are usually fragile in practical applications due to their sparse cross-linking networks, low solid content, and uneven structure, which further limits their practical applications. Although there have been many studies on polymer hydrogels, the continuous exploration of polymer hydrogels with better performance and lower cost to meet different application requirements plays an important role in the high-quality development of the hydrogel industry.

[0003] CN111363106A discloses a high-strength and high-toughness nanocomposite hydrogel, and its preparation method and application. The aqueous dispersion of CPO and ANF and the aqueous solution of PVA are compounded to form a uniform slurry, and an isotropic composite film is prepared by inorganic ion polymerization and self-assembly; then a hydrogel film with a hierarchical and ordered structure is prepared, and then a recyclable high-strength and tough composite hydrogel is obtained after stacking, bonding, applying force, drying, and swelling. The invention uses surfactant stripping and vinylated molybdenum disulfide nanosheets as cross-linking agents and fillers at the same time, which has insufficient rigidity, weak ability to support the gel network, and a complex preparation process.

[0004] Research has found that there are many things that can be learned from natural hydrogel products, such as the perfect combination of globulin silk and mesh cross-linked structure of spider webs, which can withstand large external stress; the adhesive hydrogel in mussels has a tensile strength of more than 20MPa due to its strong adhesion; human skin is a strong, water-rich, flexible interface system with highly developed structural complexity, and can also provide strong sensitivity and elasticity to changes in the external environment and self-repair capabilities. Based on the defects of current synthetic gels and the inspiration given by the superior performance of natural hydrogels, the present invention conducts comprehensive development from multiple aspects such as network structure level, polar interactions in gels, and cross-linking of nanomaterials, aiming to obtain high-strength and high-toughness hydrogel materials. Summary of the invention

[0005] The present invention overcomes the deficiencies of the above-mentioned prior art and provides a high-strength and high-toughness hydrogel based on nano-crosslinking and a preparation method thereof. Styrene monomer, sodium hexadecyl sulfonate and potassium persulfate are stirred and reacted in a water bath to prepare a styrene microsphere emulsion; using styrene microspheres as templates, vinyl triethoxysilane, ammonia water and water are added and magnetically stirred and reacted in a water bath to obtain a PS@SiO2 microsphere emulsion, and after washing, centrifugation and drying, inorganic nano-microspheres containing double bonds on the surface are obtained, and then the inorganic nano-microspheres are successively immersed and polymerized in the first, second and third covalent network crosslinking liquids to obtain a high-strength and high-toughness hydrogel based on nano-crosslinking, which has potential application prospects in the fields of ligament structure, biomaterials and the like.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing a high-strength, high-toughness hydrogel based on nano-crosslinking, specifically comprising the following steps:

[0008] (1) Preparation of inorganic nanoparticles containing double bonds:

[0009] ① Stir styrene monomer, sodium hexadecyl sulfonate, potassium persulfate and water in a water bath to make styrene microsphere emulsion;

[0010] ② Using the styrene microsphere emulsion obtained in step ① as a template, adding vinyl triethoxysilane, ammonia water and water, and reacting under magnetic stirring in a water bath to obtain PS@SiO2 microsphere emulsion, and then washing, centrifuging, drying and grinding to obtain inorganic nano-microspheres with double bonds on the surface;

[0011] (2) mixing the inorganic nanospheres obtained in step (1) with the first type of covalent network crosslinking liquid, pouring into a polytetrafluoroethylene mold, and photopolymerizing to obtain a white translucent hydrogel PSi-PEGDA;

[0012] (3) soaking the PSi-PEGDA obtained in step (2) in a second type of covalent network crosslinking solution, taking it out, and polymerizing it through light to obtain a white hydrogel PSi-PEGDA-AA;

[0013] (4) The PSi-PEGDA-AA obtained in step (3) is taken out after being immersed in a third type of covalent network cross-linking liquid, and thermally polymerized in an oxygen-free environment to obtain a high-strength and high-toughness hydrogel.

[0014] Furthermore, the styrene microsphere emulsion in step ① comprises the following raw materials by mass: 30-50 parts of styrene monomer, 0.06-0.1 parts of sodium hexadecyl sulfate, 0.05-0.2 parts of potassium persulfate, and 90-110 parts of water; the particle size of the styrene microspheres is 90-120 nm.

[0015] Furthermore, in step ①, the water bath temperature is 85-95° C.; the stirring reaction speed is 50-70 rpm, and the time is 6-10 h.

[0016] Furthermore, the PS@SiO2 microsphere emulsion in step ② comprises the following raw materials by mass: 3-7 parts of styrene microspheres, 1-5 parts of vinyltriethoxysilane, 0.1-0.5 parts of ammonia water, and 90-110 parts of water; the particle size of the PS@SiO2 microspheres is 100-150nm; the water bath temperature is 35-45°C; the magnetic stirring reaction speed is 50-70rpm, and the time is 5-8h.

[0017] Furthermore, in step ②, the washing is performed with anhydrous ethanol for 2-3 times; the centrifugal speed is 3500-4000 rpm, and the time is 15-25 min; the drying temperature is 50-70° C., and the time is 25-40 min.

[0018] Furthermore, the inorganic nanospheres in step (2) are 1-3 parts by weight; the first type of covalent network cross-linking liquid is prepared by mixing the following raw materials by weight at 25-35° C. for 10-30 minutes: 10-20 parts of ester monomers, 0.5-2 parts of poly(ethylene glycol) diacrylate (PEGDA), 1-5 parts of acrylic acid, 0.05-0.15 parts of azobisisobutyronitrile, and 4-7 parts of water.

[0019] Furthermore, in step (2), the diameter of the polytetrafluoroethylene mold is 1-2 cm and the height is 2-3 cm; the wavelength of the light polymerization is 160-200 nm and the time is 20-40 min.

[0020] Furthermore, the ester monomer in step (2) is any one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxymethyl acrylate, hydroxypropyl acrylate, and hydroxymethyl methacrylate; and the molecular weight of the poly(ethylene glycol) diacrylate (PEGDA) is 400 to 1000.

[0021] Furthermore, in step (3), the second type of covalent network cross-linking liquid is mixed by the following raw materials in parts by weight: 5 to 10 parts of acrylamide monomer (AA), 1 to 4 parts of N-isopropylacrylamide, and 2 to 5 parts of methacrylic acid; the immersion time is 25 to 35 minutes; the light polymerization wavelength is 160 to 200 nm, and the time is 20 to 30 minutes.

[0022] Furthermore, the third type of covalent network cross-linking liquid in step (4) is prepared by mixing the following raw materials in parts by weight: 8-12 parts of sulfobetaine methacrylate (SBMA), 0.1-1 parts of N,N-methylenebisacrylamide, 0.05-0.2 parts of potassium persulfate, and 1-5 parts of water; the immersion time is 10-20 minutes; the thermal polymerization temperature is 80-100° C., and the time is 20-40 minutes.

[0023] The invention provides a high-strength and high-toughness hydrogel based on nano-crosslinking prepared by the preparation method.

[0024] The present invention also provides the application of the high-strength and high-toughness hydrogel based on nano-crosslinking in the field of ligament structure or biomaterials.

[0025] Beneficial effects:

[0026] (1) The present invention provides a high-strength, toughened hydrogel material based on nano-crosslinking. Compared with the traditional multiple crosslinking, the present invention first prepares crosslinkable inorganic nano-microspheres, the surface of which contains double bonds, which are easily copolymerized with PEGDA monomers to form the first layer of covalent network crosslinking structure supported by the microspheres, and the crosslinked nano-microspheres can be evenly dispersed in the entire system, which not only plays a chemical crosslinking role, but also plays a physical reinforcement role; the introduction of monomers acrylic acid and methacrylic acid in the second type of covalent network crosslinking liquid is aimed at forming a second layer of covalent crosslinking support structure, and the monomers contain carboxyl groups to form a large number of hydrogen bonds, thereby increasing non-covalent forces and further improving mechanical properties. The monomers sulfobetaine methacrylate and N,N-methylenebisacrylamide in the third type of covalent network crosslinking liquid have larger molecular structures, which play a role in strengthening the network structure and improving mechanical properties. The inorganic microsphere nanomaterial, the three-component covalent crosslinking structure, and the non-covalent forces synergistically improve the mechanical properties of the material, and a high-strength, high-toughness hydrogel with triple nano crosslinking is obtained.

[0027] (2) The preparation process of the present invention is easy to control, convenient to operate, and has mild reaction conditions. The obtained hydrogel has potential application prospects in the fields of ligament structure, biomaterials, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Figure 1 shows a high-strength and high-toughness hydrogel based on nano-crosslinking with reduced water content;

[0029] Figure 2 This is a transmission electron microscope image of inorganic nanospheres;

[0030] Figure 3 This is a trend chart of the compressive strength of high-strength and high-toughness hydrogels. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be specifically described below in conjunction with the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0032] Example 1

[0033] 1. A method for preparing a high-strength and high-toughness hydrogel based on nano-crosslinking, comprising the following steps:

[0034] (1) Preparation of inorganic nanoparticles containing double bonds:

[0035] ① According to the mass fraction, 40 parts of styrene monomer, 0.08 parts of sodium hexadecyl sulfonate, a surfactant, 100 parts of water, and 0.1 parts of potassium persulfate, a catalyst, were stirred at 60 rpm for 8 hours at a water bath temperature of 90°C to prepare a styrene microsphere emulsion with a particle size of 100 nanometers;

[0036] ② Using 5 parts by mass of the styrene microsphere emulsion obtained in step ① as a template, 3 parts of vinyl triethoxysilane, 100 parts of water, and 0.3 parts of ammonia water were added, and the reaction was carried out at a water bath temperature of 40°C and a magnetic stirring of 60 rpm for 6 hours to obtain a PS@SiO2 microsphere emulsion with a particle size of 120 nm, which was washed twice with anhydrous ethanol, centrifuged at 3800 rpm for 20 minutes, and finally dried at 60°C for 30 minutes to obtain inorganic nano-microspheres with double bonds on the surface;

[0037] (2) preparing a first type of covalent network crosslinking liquid, which is prepared by mixing the following raw materials by weight at 30° C. for 20 minutes: 15 parts of hydroxyethyl acrylate monomer, 1 part of poly(ethylene glycol) diacrylate (PEGDA) with a molecular weight of 500, 3 parts of acrylic acid, 0.1 parts of photoinitiator azobisisobutyronitrile, and 5 parts of water; taking 1 part of the inorganic nanospheres obtained in step (1) and mixing it with the first type of covalent network crosslinking liquid to form a white translucent mixed liquid, pouring it into a polytetrafluoroethylene column mold with a diameter of 1.5 cm and a height of 2.5 cm, and polymerizing it under ultraviolet light with a wavelength of 180 nm for 20 minutes to obtain a white translucent hydrogel PSi-PEGDA;

[0038] (3) soaking the PSi-PEGDA obtained in step (2) in a second type of covalent network crosslinking solution composed of 8 parts of acrylamide monomer (AA), 2 parts of N-isopropyl acrylate, and 3 parts of methacrylic acid, taking it out after soaking for 30 minutes, and polymerizing it under ultraviolet light with a wavelength of 180 nm for 25 minutes to obtain a white hydrogel PSi-PEGDA-AA;

[0039] (4) The PSi-PEGDA-AA obtained in step (3) is immersed in a third type of covalent network crosslinking solution consisting of 10 parts of sulfobetaine methacrylate (SBMA), 0.5 parts of N,N-methylenebisacrylamide, 0.1 parts of potassium persulfate, and 2 parts of water, and is taken out after immersion for 15 minutes, and is thermally polymerized at 90° C. in an oxygen-free environment for 30 minutes to obtain a white hydrogel. Figure 1 shown.

[0040] 2. Performance Analysis

[0041] (1) Electron microscopy observation: The inorganic nanospheres obtained above were observed using a transmission electron microscope. Figure 2 The monodisperse microspheres in the figure are inorganic nano-microspheres. A circle of black stripes can be seen on the surface of the balls. The outside of the stripes is a silicon dioxide layer containing double bonds, and the inside is styrene microspheres. The interface is clearly visible in the transmission electron microscopy image, which is a "core-shell" structure, indicating that inorganic nano-microspheres containing double bonds on the surface have been synthesized.

[0042] (2) Mechanical property testing: The white hydrogel (PSi-PEGDA-AA-SBMA) obtained above has a cylindrical structure with a diameter of 1.5 cm and a height of 2.5 cm. The hydrogel was tested at room temperature using a universal mechanical equipment compression mode with a compression rate of 1 mm / min and the test was repeated 1000 times.

[0043] like Figure 3 From the compression resistance curve of the hydrogel, it can be seen that when the strain is 0.8, the compression strength reaches 8.4MPa, indicating that a stronger compression resistance is obtained under a smaller compression strain. This is because the hydrogel contains a large number of non-covalent hydrogen bonds that dissipate a large amount of force, the covalent bond network serves as a supporting skeleton, and the inorganic nano-microspheres increase the rigidity. The internal structures work synergistically. Even after 1000 cycles of compression, the internal dissipation of the network is strong, which can ensure that the compression curve remains basically unchanged.

[0044] Example 2

[0045] 1. A method for preparing a high-strength and high-toughness hydrogel based on nano-crosslinking, comprising the following steps:

[0046] (1) Preparation of inorganic nanoparticles containing double bonds:

[0047] ① According to the mass fraction, 40 parts of styrene monomer, 0.08 parts of sodium hexadecyl sulfonate, a surfactant, 100 parts of water, and 0.1 parts of potassium persulfate, a catalyst, were stirred at 60 rpm for 8 hours at a water bath temperature of 90°C to prepare a styrene microsphere emulsion with a particle size of 100 nanometers;

[0048] ② Using 5 parts by mass of the styrene microsphere emulsion obtained in step ① as a template, 3 parts of vinyl triethoxysilane, 100 parts of water, and 0.3 parts of ammonia water were added, and the reaction was carried out at a water bath temperature of 40°C and a magnetic stirring of 60 rpm for 6 hours to obtain a PS@SiO2 microsphere emulsion with a particle size of 120 nm, which was washed twice with anhydrous ethanol, centrifuged at 3800 rpm for 20 minutes, and finally dried at 60°C for 30 minutes to obtain inorganic nano-microspheres with double bonds on the surface;

[0049] (2) preparing a first type of covalent network crosslinking liquid, which is prepared by mixing the following raw materials by weight at 30° C. for 20 minutes: 15 parts of hydroxyethyl acrylate monomer, 1 part of poly(ethylene glycol) diacrylate (PEGDA) with a molecular weight of 800, 3 parts of acrylic acid, 0.1 parts of photoinitiator azobisisobutyronitrile, and 5 parts of water; taking 2 parts by weight of the inorganic nanospheres obtained in step (1) and mixing them with the first type of covalent network crosslinking liquid to form a white translucent mixed liquid, pouring it into a polytetrafluoroethylene column mold with a diameter of 1.5 cm and a height of 2.5 cm, and polymerizing it under ultraviolet light with a wavelength of 180 nm for 30 minutes to obtain a white translucent hydrogel PSi-PEGDA;

[0050] (3) soaking the PSi-PEGDA obtained in step (2) in a second type of covalent network crosslinking solution composed of 8 parts of acrylamide monomer (AA), 2 parts of N-isopropyl acrylate, and 3 parts of methacrylic acid, taking it out after soaking for 30 minutes, and polymerizing it under ultraviolet light with a wavelength of 180 nm for 25 minutes to obtain a white hydrogel PSi-PEGDA-AA;

[0051] (4) The PSi-PEGDA-AA obtained in step (3) is immersed in a third type of covalent network crosslinking solution consisting of 10 parts of sulfobetaine methacrylate (SBMA), 0.5 parts of N,N-methylenebisacrylamide, 0.1 parts of potassium persulfate, and 2 parts of water, and taken out after immersion for 15 minutes, and thermally polymerized at 90° C. in an oxygen-free environment for 30 minutes to obtain a white hydrogel.

[0052] 2. Performance Analysis

[0053] The compressive strength of the hydrogel obtained in this embodiment is tested to be 10.5 MPa. It can be seen that increasing the content of inorganic nanospheres and the molecular weight of PEGDA and increasing the photopolymerization time improves the compressive strength of the hydrogel. This is because increasing the content of inorganic nanospheres is beneficial to enhancing the rigid support capacity of the hydrogel, and the double bonds on the surface can be polymerized with more monomers; the increase in the molecular weight of PEGDA makes the network cross-linking tighter; the increase in photopolymerization time is beneficial to monomer polymerization, and the covalent bond cross-linking is more sufficient, and the compressive strength of the obtained hydrogel is further improved.

[0054] Example 3

[0055] 1. A method for preparing a high-strength and high-toughness hydrogel based on nano-crosslinking, comprising the following steps:

[0056] (1) Preparation of inorganic nanoparticles containing double bonds:

[0057] ① According to the mass fraction, 40 parts of styrene monomer, 0.08 parts of sodium hexadecyl sulfonate, a surfactant, 100 parts of water, and 0.1 parts of potassium persulfate, a catalyst, were stirred at 60 rpm for 8 hours at a water bath temperature of 90°C to prepare a styrene microsphere emulsion with a particle size of 100 nanometers;

[0058] ② Using 5 parts by mass of the styrene microsphere emulsion obtained in step ① as a template, 3 parts of vinyl triethoxysilane, 100 parts of water, and 0.3 parts of ammonia water were added, and the reaction was carried out at a water bath temperature of 40°C and a magnetic stirring of 60 rpm for 6 hours to obtain a PS@SiO2 microsphere emulsion with a particle size of 120 nm, which was washed twice with anhydrous ethanol, centrifuged at 3800 rpm for 20 minutes, and finally dried at 60°C for 30 minutes to obtain inorganic nano-microspheres with double bonds on the surface;

[0059] (2) preparing a first type of covalent network crosslinking liquid, which is prepared by mixing the following raw materials by weight at 30° C. for 20 minutes: 15 parts of hydroxyethyl acrylate monomer, 1 part of poly(ethylene glycol) diacrylate (PEGDA) with a molecular weight of 500, 3 parts of acrylic acid, 0.1 parts of photoinitiator azobisisobutyronitrile, and 5 parts of water; taking 2 parts by weight of the inorganic nanospheres obtained in step (1) and mixing them with the first type of covalent network crosslinking liquid to form a white translucent mixed liquid, pouring it into a polytetrafluoroethylene column mold with a diameter of 1.5 cm and a height of 2.5 cm, and polymerizing it under ultraviolet light with a wavelength of 180 nm for 35 minutes to obtain a white translucent hydrogel PSi-PEGDA;

[0060] (3) soaking the PSi-PEGDA obtained in step (2) in a second type of covalent network crosslinking solution composed of 8 parts of acrylamide monomer (AA), 2 parts of N-isopropyl acrylate, and 3 parts of methacrylic acid, taking it out after soaking for 30 minutes, and polymerizing it under ultraviolet light with a wavelength of 180 nm for 25 minutes to obtain a white hydrogel PSi-PEGDA-AA;

[0061] (4) The PSi-PEGDA-AA obtained in step (3) is immersed in a third type of covalent network crosslinking solution consisting of 10 parts of sulfobetaine methacrylate (SBMA), 0.5 parts of N,N-methylenebisacrylamide, 0.1 parts of potassium persulfate, and 2 parts of water, and taken out after immersion for 15 minutes, and thermally polymerized at 90° C. in an oxygen-free environment for 30 minutes to obtain a white hydrogel.

[0062] 2. Performance Analysis

[0063] The hydrogel obtained in this example was tested to have a compressive strength of 9.3 MPa. Compared with Example 1, while ensuring that the molecular weight of PEGDA and other conditions remain unchanged, it was further verified that increasing the content of inorganic nanospheres and the light polymerization time are beneficial to improving the mechanical properties of the hydrogel.

Claims

1. A method for preparing a high-strength and high-toughness hydrogel based on nano-crosslinking, characterized in that: The method comprises the following specific steps: (1) Preparation of inorganic nanoparticles containing double bonds: ① Stir styrene monomer, sodium hexadecyl sulfonate, potassium persulfate and water in a water bath to make styrene microsphere emulsion; ② Using the styrene microsphere emulsion obtained in step ① as a template, adding vinyl triethoxysilane, ammonia water and water, and reacting under magnetic stirring in a water bath to obtain PS@SiO2 microsphere emulsion, and then washing, centrifuging, drying and grinding to obtain inorganic nano-microspheres with double bonds on the surface; (2) mixing the inorganic nanospheres obtained in step (1) with the first type of covalent network crosslinking liquid, pouring into a polytetrafluoroethylene mold, and photopolymerizing to obtain a white translucent hydrogel PSi-PEGDA; (3) soaking the PSi-PEGDA obtained in step (2) in a second type of covalent network crosslinking solution, taking it out, and polymerizing it through light to obtain a white hydrogel PSi-PEGDA-AA; (4) The PSi-PEGDA-AA obtained in step (3) is taken out after being immersed in a third type of covalent network cross-linking liquid, and thermally polymerized in an oxygen-free environment to obtain a high-strength and high-toughness hydrogel.

2. The preparation method according to claim 1, characterized in that: Step ① The styrene microsphere emulsion comprises the following raw materials by mass: 30-50 parts of styrene monomer, 0.06-0.1 parts of sodium hexadecyl sulfonate, 0.05-0.2 parts of potassium persulfate, and 90-110 parts of water; the water bath temperature is 85-95° C.; the stirring reaction speed is 50-70 rpm, and the time is 6-10 hours; the particle size of the styrene microspheres is 90-120 nm.

3. The preparation method according to claim 1, characterized in that: Step ② The PS@SiO2 microsphere emulsion includes the following raw materials by mass: 3-7 parts of styrene microspheres, 1-5 parts of vinyl triethoxysilane, 0.1-0.5 parts of ammonia water, and 90-110 parts of water; the particle size of the PS@SiO2 microspheres is 100-150nm; the water bath temperature is 35-45°C; the magnetic stirring reaction speed is 50-70rpm, and the time is 5-8h; the washing is 2-3 times with anhydrous ethanol; the centrifugal speed is 3500-4000rpm, and the time is 15-25min; the drying temperature is 50-70°C, and the time is 25-40min.

4. The preparation method according to claim 1, characterized in that: The inorganic nano-microspheres in step (2) are 1-3 parts by weight; the first type of covalent network cross-linking liquid is prepared by mixing the following raw materials by weight at 25-35° C. for 10-30 minutes: 10-20 parts of ester monomers, 0.5-2 parts of poly(ethylene glycol) diacrylate, 1-5 parts of acrylic acid, 0.05-0.15 parts of azobisisobutyronitrile, and 4-7 parts of water; the polytetrafluoroethylene mold has a diameter of 1-2 cm and a height of 2-3 cm; the light polymerization wavelength is 160-200 nm and the time is 20-40 minutes.

5. The preparation method according to claim 4, characterized in that: The ester monomer in step (2) is any one of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxymethyl acrylate, hydroxypropyl acrylate and hydroxymethyl methacrylate.

6. The preparation method according to claim 4, characterized in that: The molecular weight of the poly(ethylene glycol) diacrylate in step (2) is 400 to 1000.

7. The preparation method according to claim 1, characterized in that: Step (3) The second type of covalent network cross-linking liquid is mixed by the following raw materials in parts by weight: 5 to 10 parts of acrylamide monomer, 1 to 4 parts of N-isopropylacrylamide, and 2 to 5 parts of methacrylic acid; the immersion time is 25 to 35 minutes; the light polymerization wavelength is 160 to 200 nm, and the time is 20 to 30 minutes.

8. The preparation method according to claim 1, characterized in that: The third type of covalent network cross-linking liquid in step (4) is prepared by mixing the following raw materials in parts by weight: 8-12 parts of sulfobetaine methacrylate, 0.1-1 parts of N,N-methylenebisacrylamide, 0.05-0.2 parts of potassium persulfate, and 1-5 parts of water; the immersion time is 10-20 minutes; the thermal polymerization temperature is 80-100°C, and the time is 20-40 minutes.

9. A high-strength, high-toughness hydrogel based on nano-crosslinking prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the high-strength and high-toughness hydrogel based on nano-crosslinking according to claim 9 in the preparation of ligament structures or biomaterials.

Citation Information

Patent Citations

  • High-strength and high-toughness nano composite hydrogel and preparation method and application thereof

    CN111363106A